IMBALANCED SEX RATIOS, MEN’S SEXUAL BEHAVIOR, AND STI RISK IN CHINA(*) - South, Scott J. (2010)
China has been experiencing pronounced changes in its sex ratio, but little research has explored the consequences of these changes for sexual behavior and health. We merge data from the 1999–2000 Chinese Health and Family Life Survey with community-level data from the 1982, 1990, and 2000 Chinese censuses to examine the relationship between the local sex ratio and several dimensions of men’s sexual behavior and sexual health. Multilevel logistic regression models show that, when faced with a relative abundance of age-matched women in their community, Chinese men are slightly less likely to have intercourse with commercial sex workers, but are more likely to engage in premarital noncommercial intercourse and to test positive for a sexually-transmitted infection (STI). These findings are consistent with hypotheses derived from demographic-opportunity theory, which suggests that an abundance of opposite-sex partners will increase the risk of early, frequent, and multi-partner sex and, through this, STI risk.